2015
DOI: 10.1155/2015/108247
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality following Traditional Uvulectomy among Children Presenting to the Muhimbili National Hospital Emergency Department in Dar es Salaam, Tanzania

Abstract: Background. Traditional uvulectomy is performed as a cultural ritual or purported medical remedy. We describe the associated emergency department (ED) presentations and outcomes. Methods. This was a subgroup analysis of a retrospective review of all pediatric visits to our ED in 2012. Trained abstracters recorded demographics, clinical presentations, and outcomes. Results. Complete data were available for 5540/5774 (96%) visits and 56 (1.0%, 95% CI: 0.7–1.3%) were related to recent uvulectomy, median age 1.3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…The most common reason for traditional uvulectomy is upper respiratory infection. [14] Sawe et al [7] in their study reported that the final diagnosis in patients who were Section: Dentistry brought to hospital following uvulectomy included pneumonia, malaria, severe anaemia, malnutrition, tuberculosis and bronchitis. Majority of the participants in the current study had awareness regarding traditional treatment modalities for managing a diseased uvula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common reason for traditional uvulectomy is upper respiratory infection. [14] Sawe et al [7] in their study reported that the final diagnosis in patients who were Section: Dentistry brought to hospital following uvulectomy included pneumonia, malaria, severe anaemia, malnutrition, tuberculosis and bronchitis. Majority of the participants in the current study had awareness regarding traditional treatment modalities for managing a diseased uvula.…”
Section: Discussionmentioning
confidence: 99%
“…The reported traditional methods that were known included smearing the uvula with local herbs and cutting the uvula with a sharp edged instrument. Use of sharp objects which are unsterile has been documented in various literatures [2,4,6,7,17] and use of local herbs has likewise been documented. [2,18] Almost half of the participants were aware of traditional methods used in treating what was perceived to be a diseased uvula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators from Carolinas Medical Center have a history of successful enrolment of MNH ED patients in several prior and ongoing investigations. [57][58][59][60][61] Our institution also has direct ties to MBH in Cameroon, where one of our study authors previously served as the chief of paediatrics. Current and former personnel from MBH have successfully collaborated on numerous national and international research investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Uvulectomy was not endemic to Morocco, but was widely practiced in African tribes. The procedure was performed by tribal healers based on the belief that it was preventative for throat and chest infections [16] .…”
Section: Surgical Proceduresmentioning
confidence: 99%